EXPLORING THE PSYCHOLOGICAL MECHANISMS OF DÉJÀ VU: A CROSS-SECTIONAL STUDY ON THE RELATIONSHIP BETWEEN MEMORY, PERCEPTION, AND COGNITIVE BIASES IN ADULTS (The Research of Medical Science Review, 2024)
Déjà vu, the sensation of having previously experienced a current situation, remains an intriguing phenomenon with unclear underlying psychological mechanisms. This study examines the relationships between cognitive biases, memory recall accuracy, perceptual processing accuracy, and the occurrence and intensity of déjà vu experiences in university students, To explore the psychological mechanisms underlying déjà vu by assessing the impact of cognitive biases, memory distortions, and perceptual processing inconsistencies on déjà vu experiences, A cross-sectional study was conducted with 180 university students aged 18-30 years. Participants completed the Cognitive Bias Questionnaire (CBQ) and provided data on memory recall accuracy and perceptual processing accuracy. Descriptive statistics, Pearson correlation, and multiple regression analyses were employed to examine the relationships between these variables and déjà vu occurrences, The study found significant positive correlations between cognitive biases and both the frequency (r = 0.48, p < .01) and intensity (r = 0.52, p < .01) of déjà vu experiences. Poorer memory recall accuracy was negatively correlated with déjà vu frequency (r = -0.36, p < .01) and intensity (r = -0.40, p < .01), while less accurate perceptual processing was also negatively correlated with déjà vu frequency (r = -0.29, p < .05) and intensity (r = -0.32, p < .05). Multiple regression analysis indicated that cognitive biases (β = 0.35, p < .001) were the strongest predictor of déjà vu, followed by memory recall accuracy (β = -0.22, p < .001) and perceptual processing accuracy (β = -0.15, p = .034). The model explained 45% of the variance in déjà vu experiences (R² = 0.45), The findings suggest that déjà vu is significantly influenced by cognitive biases, memory distortions, and perceptual processing errors. Cognitive biases were identified as the strongest predictor of déjà vu experiences. These results enhance our understanding of the psychological mechanisms underlying déjà vu and highlight the importance of considering multiple psychological factors in future research.